Theoretical Inquiries in Law (De Gruyter, 2000)
Theoretical Inquiries in Law (TIL) is devoted to the application to legal thought of insights developed by diverse disciplines such as philosophy, sociology, economics, history and psychology. The range of legal issues dealt with by the journal is virtually unlimited, subject only to the journal's commitment to cross-disciplinary fertilization of ideas.